A community-based epidemiological study of periodontal disease in Keelung, Taiwan: a model from Keelung community-based integrated screening programme (KCIS No. 18) - Hongmin Lai (Blackwell Synergy, 2007)
Aims: To estimate the prevalence and severity of periodontal disease (PD) in the Taiwanese population aged 35–44 years and to investigate the association between demographic factors and PD. Materials and Methods: Between 2003 and 2005, residents of Keelung of the appropriate age were invited to screening. The community periodontal index (CPI) and loss of attachment (LA) index were used to measure the periodontal status at subject (prevalence) and sextant levels (severity). Basic demographic information was also collected by a questionnaire. Results: Of 8462 enrollees, 94.8% had some signs of PD, of whom 29.7% had periodontal pockets 43mm and 35% LA 43 mm. Calculus was the most common problem in terms of both prevalence (49.6%) and severity (affecting an average of 3.0 sextants per person). Risk factors for poor periodontal status (as measured by CPI) were older age (odds ratio, OR: 1.44), male gender (OR: 2.70), low education level (OR: 1.40), and being a manual worker (OR: 1.51). Similar findings were observed for LA. Conclusion: The prevalence of PD in 35–44-year-olds was found to be high in this large community-based study of screening for PD with CPI and LA. Poorer periodontal health was observed in males, the less educated, and manual workers.